Development and pilot testing of a Patient Blood Management App to guide junior doctor clinical decision making on red cell transfusions in non bleeding adult patients – results of accuracy study - Dhesi, A; Wyatt, J; Estcourt, L; McSporran, W; McCullagh, J; Allard, S; Katic, S (Wiley, 2017)
Patient Blood Management (PBM) is a patient-centred approach to blood transfusion promoting blood use only when appropriate with alternatives substituted wherever feasible. Successive audits have shown inappropriate use of 15–30% of blood components. With funding from NHS Blood and Transplant we developed a Smartphone Application (App) aimed at improving junior doctor compliance with transfusion guidelines and reducing inappropriate red cell transfusions in non bleeding adult patients, with emphasis on informed patient consent and anaemia management. The App will be CE marked as a Class 1 medical device (MHRA) to demonstrate quality.